2018
DOI: 10.1007/s11418-018-1210-1
|View full text |Cite
|
Sign up to set email alerts
|

Berberine protects renal tubular cells against hypoxia/reoxygenation injury via the Sirt1/p53 pathway

Abstract: Berberine (BBR) has been demonstrated to protect against renal ischemia/reperfusion injury; however, the underlying molecular mechanism is largely unknown. In the present study, we examined the role of silent information regulator 1 (Sirt1)/p53 in the protective effect of BBR on hypoxia/reoxygenation (H/R)-mediated mitochondrial dysfunction in rat renal tubular epithelial cells (NRK-52E cells). NRK-52E cells were preconditioned with small interfering RNA targeting Sirt1 (Sirt1-siRNA) and BBR before subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…As shown in Figure 6A, while the nuclei of the cells were round in shape homogenously in the control without the testing compound, those treated with berberine (1), compound 5e, 6e, or 7e showed typical morphological features of apoptosis such as cell blebbing and nuclear shrinkage. Figure 6B shows that HepG2 cells treated with 0.5 µM of compound 7e stained with Hoechst 33,258 in dark or light, and examined under fluorescence microscopy for topical morphological changes, such as chromatin condensation and DNA fragmentation [34]. Evidently, the proliferation of the cancer cells was inhibited by the testing compounds in vitro.…”
Section: Cell Morphological Assessmentmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Figure 6A, while the nuclei of the cells were round in shape homogenously in the control without the testing compound, those treated with berberine (1), compound 5e, 6e, or 7e showed typical morphological features of apoptosis such as cell blebbing and nuclear shrinkage. Figure 6B shows that HepG2 cells treated with 0.5 µM of compound 7e stained with Hoechst 33,258 in dark or light, and examined under fluorescence microscopy for topical morphological changes, such as chromatin condensation and DNA fragmentation [34]. Evidently, the proliferation of the cancer cells was inhibited by the testing compounds in vitro.…”
Section: Cell Morphological Assessmentmentioning
confidence: 97%
“…The apoptotic cells change in morphology, such as chromatin condensation, nuclear shrinking, and DNA fragmentation. It can be characterized through Hoechst 33,258 stained cell nucleus [34] under a fluorescent microscope. Thus, to further study the role of apoptosis played in the superior cytotoxicity of compounds 5e, 6e, and 7e, we incubated HepG2 cells in 0.5 µM of berberine (1), or its three derivatives separately.…”
Section: Cell Morphological Assessmentmentioning
confidence: 99%
“…In recent years with regard to the side effects of artificial medicines, increasing attention has been paid by researchers to herbal medicines. Our in vivo study revealed that treatment with BER‐chloride has negative influence on insulin resistance through activating two proteins involved in several physiological processes, SIRT‐1 and AMPK (Lin et al, ). Those two proteins able to activate each other, AMPK activate SIRT‐1 by elevation the concentration of nicotinamide phosphoribosyltransferase and SIRT‐1 stimulates AMPK through deacetylation of serine‐threonine kinase LKB1 (Hardie, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Our in vivo study revealed that treatment with BER-chloride has negative effect on insulin resistance by activating two proteins involved in several physiological processes, SIRT-1 and AMPK [49]. Those two proteins able to activate each other, AMPK activates SIRT-1 by elevation the level of nicotinamide phosphoribosyltransferase and SIRT-1 stimulates AMPK through deacetylation of serine-thereonine kinase LKB1 [50, 51].…”
Section: Discussionmentioning
confidence: 99%